Values Evolution in Transitional China: An Institutional Perspective - Sun, Gong; Li, Jian (Frontiers in Psychology, 2021)
The values are greatly affected by the social and economic environment of a country. Thus, social transformation can lead to the values evolution. China has been experiencing a huge social, political, and economic transition in the past four decades. The previous studies that explore the value changes in China mainly compare the values across the regions or generation cohorts. This research investigates the issue from an institutional perspective. Specifically, we propose that the diversification of ownership types—the essence of the economic and institutional reform since 1978 may result in value change. By surveying 327 participants from the state-owned enterprises (SOEs) and 220 respondents from the privately owned enterprises (POEs), the comparisons between SOEs and POEs on four value dimensions—individualism, power distance, risk aversion, and money orientation—were performed. The results basically support cross-vergence theory in the values evolution. The implications and limitations are presented as well.